Analisis Yuridis Kebijakan TKDN terhadap Kepastian Hukum Penanaman Modal Asing di Sektor Teknologi di Indonesia - Muhammad Alldo Hibahtillah; Sang Ayu Putu Rahayu; Duhita Driyah Suprapti (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Factually, the implementation of Local Content Requirements (LCR), known in Indonesia as the Domestic Component Level (TKDN), presents both opportunities and challenges in relation to foreign direct investment. This study aims to analyze the legal framework governing TKDN policies in Indonesia and to examine their impact on foreign investment. This research uses a qualitative method with a descriptive approach through the analysis of primary and secondary data. The results show that TKDN policy has been regulated through various laws and regulations, including Law Number 3 of 2014 concerning Industry and Government Regulation Number 29 of 2018. The policy aims to strengthen domestic industries, reduce dependence on imports, and encourage technology transfer. However, in practice, the implementation of TKDN still faces several obstacles, such as regulatory complexity, limited domestic industrial capacity, and increased production costs for foreign investors. Therefore, improvements in regulatory clarity, industrial capacity, and policy implementation are necessary to ensure that TKDN policies can be carried out effectively without reducing investment attractiveness .